THE EFFECT OF SPECIAL EXERCISES ON DEVELOPING ATTENTION ASPECTS AND THE PERFORMANCE OF SOME TABLE TENNIS SKILLS FOR PLAYERS AGED (12-14) YEARS - Taqi, Israa Hassan Mohammed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The attribute of speed serves the motor performance and gives it the required effectiveness, and the attributes of strength and speed together serve the motor performance so that it performs properly and effectively, thus the ability to score points in the shortest possible time and win against the competitor. The importance of the research lies in preparing special exercises to develop attention aspects and the forehand and backhand skills in table tennis for players according to the correct performance of the skill. From this standpoint, the researcher turned to this study, believing that these special exercises will contribute to developing the physical and skill levels of table tennis players. The research problem was noticed by the researchers through their previous experiences as practitioners of the game in the weakness of attention aspects among table tennis players. The researcher believes that the reason for this is that most coaches do not use modern devices during their training for skills, as they usually rely on traditional methods in implementing and teaching the skill to beginners. Therefore, the researcher decided to add some modern techniques during her study of this problem by trying to use special exercises to develop attention aspects and some table tennis skills for players. The research aims to prepare special exercises to develop attention aspects and some table tennis skills for players, and to identify the effect of special exercises in developing attention aspects and some table tennis skills for players, Conclusions, the results showed that there is a positive effect of special exercises in developing attention aspects (focus – transfer – distribution) among table tennis players aged (12-14) years. The results also showed that there is a positive effect of special exercises in developing some table tennis skills for players aged (12-14) years.